2018
DOI: 10.5539/jas.v10n9p64
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Roselle (Hibiscus sabdariffa L. var. altissima Wester) Accessions in Northern Ghana by Agro-morphological Traits

Abstract: Roselle (Hibiscus sabdariffa L. var. altissima Wester) is a bast fiber crop of global economic importance. Although West Africa is considered the centre of diversity, roselle research and utilization is widely ignored. The awakening of industrialization in Ghana presents roselle as a candidate crop for exploration, however, information on genotypes of economic importance is lacking. Our objective was to map roselle population hotspots in northern Ghana and examine genetic variability therein. Thirty-six rosell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…sabdariffa, however, 39% had yellow petals and 91% crimson throat. The qualitative characteristics of roselle concur with an earlier report on 36 roselle fibre genotypes from northern Ghana (Ankrah et al, 2018), which exhibited ample variability in plant type, branching habit, stem pubescence and leaf form. The absence of variability in growth habit, calyx pubescence and capsule shape indicates that these traits are conserved in roselle (var.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…sabdariffa, however, 39% had yellow petals and 91% crimson throat. The qualitative characteristics of roselle concur with an earlier report on 36 roselle fibre genotypes from northern Ghana (Ankrah et al, 2018), which exhibited ample variability in plant type, branching habit, stem pubescence and leaf form. The absence of variability in growth habit, calyx pubescence and capsule shape indicates that these traits are conserved in roselle (var.…”
Section: Discussionsupporting
confidence: 89%
“…Current bast fibre production in SSA amounts to 16,000 metric tons/year. Research and development in roselle as a potential for bast fibre production in Ghana is lacking, despite a wide range of morphotypes found in the northern sector of the country (Ankrah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High genetic diversity for all traits except throat/inner corolla color and plant growth habit among the accession. The large variability in stem color and leaf shape was also reported by(Ankrah et al, 2018b). While, plant growth habit and inner corolla color showed moderate diversity among the accession.…”
supporting
confidence: 63%
“…Despite these drawbacks, morphological evaluation provides information on crop characteristics and reveals sources of useful genotypes for trait improvement (Camussi et al, 1985). Genetic diversity studies on roselle are rather scanty and limited to work reported by (Ankrah et al, 2018a) who assessed thirty-six wild roselle accessions in Ghana; characterization of roselle accessions by agromorphological and RAPD genotyping study in west Africa (Co e, 2016), and a comparative variability study between kenaf and roselle (Siepe et al, 1997); (Cheng et al, 2004); (Sie et al, 2009). Withinpopulation diversity measures the number of distinct classes in a population as richness and the relative abundance of genotypes within those classes as evenness (Shannon & Weaver, 1949).…”
Section: Introductionmentioning
confidence: 99%